Integrating Ethno-Realistic Mathematics Education in developing three-dimensional instructional module - Shahidayanti, Tutik; Prahmana, Rully Charitas Indra; Fran, Frankie A. (Journal of Honai Math, 2024)
The integration of cultural and realistic contexts in mathematics learning has shown significant potential in fostering critical thinking skills; however, existing educational resources often lack a comprehensive approach that effectively combines these aspects. Addressing this gap, this research aimed to develop a novel Ethno-Realistic Mathematics Education (Ethno-RME)-based three-dimensional learning module that meets the criteria of validity, practicality, and has a positive impact on students' critical thinking skills. Utilizing a Design Research methodology, specifically a development study, the research was conducted in two stages: Preliminary Evaluation and Formative Evaluation, involving 12th-grade students from SMAN 5 Purworejo as participants. Data collection included product quality assessment sheets evaluated by material and media experts, student response sheets, and critical thinking test instruments. The results demonstrated that the module achieved high validity, with content rated "Good" (average score: 141 out of 175) and media rated "Very Good" (average score: 131 out of 135). Practicality was confirmed through student responses, with small group and field test average scores classified as "Very Good" (72.33 and 72.36, respectively). Furthermore, post-test results for critical thinking skills revealed an average score of 75.51, indicating the module’s potential to enhance students’ critical thinking. These findings establish the Ethno-RME-based module as a valid, practical, and impactful teaching resource, offering a culturally relevant and application-oriented alternative for mathematics education.